2022
DOI: 10.3390/app12199935
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characterization of Selected Algae and Cyanobacteria from Bulgaria as Sources of Compounds with Antioxidant Activity

Abstract: The current research focused on algae from the waters of the Black Sea—Chaetomorpha linum, Ulva intestinalis, Ericaria crinita, and bioreactors—Chlorella spp. and Arthrospira platensis/cyanobacterium/. Pigment content, total phenolic content, and antioxidant capacity were investigated for their use as pharmaceutical, food, and cosmetic ingredients. E. crinita exhibited the highest antioxidant activity by ORAC and HORAC (463.3 µmol TE/g and 463.3 µmol GAE/g) and the highest total content of polyphenols and ruti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 79 publications
0
10
0
Order By: Relevance
“…HPLC analysis indicated that some compounds including catechin, ellagic acid, ferulic acid, daidzein, kaempferol, and hesperetin not detected according the injected standards. Gentscheva et al [33] reported the presence of naringenin and quercetin in several extracts of algae.…”
Section: Resultsmentioning
confidence: 99%
“…HPLC analysis indicated that some compounds including catechin, ellagic acid, ferulic acid, daidzein, kaempferol, and hesperetin not detected according the injected standards. Gentscheva et al [33] reported the presence of naringenin and quercetin in several extracts of algae.…”
Section: Resultsmentioning
confidence: 99%
“…This regimen resulted in a decrease in serum cholesterol, triglyceride, LDL, and VLDL levels, while there was an observable increase in the serum HDL level. Gentscheva et al [50] reported that Sp reduced serum cholesterol, triglyceride, LDL, and VLDL when volunteers were given a 4gm/day oral dose. In line with these studies, Sp (4.2 gm/day) was added for eight weeks to the diet of 30 Japanese males with high cholesterol, mild hypertension, and hyperlipidemia.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Pradhan et al (2021) conducted E. intestinalis contains 60 mg of gallic acid and 625 mg of rutin equivalents per gram of extract, in terms of total phenol and flavonoids. The study by Gentscheva et al (2022) also focused on U. intestinalis containing rutin and polyphenols as the highest total content. Phenolic compounds were detected by HPLC analysis in the work of Abu Samra et al (2023) confirmed that Enteromorpha sp.…”
Section: Discussionmentioning
confidence: 99%
“…Among the flavonoids, rutin, quercetin, naringin, kaempferol, and myricetin demonstrated the most pronounced antioxidant behavior. Quercetin exhibits superior antioxidant efficacy against free radicals that are soluble in both water and fat ( Gentscheva et al, 2022 ). Rutin, in particular, is a phytochemical with numerous biological effects, such as analgesic, antiarthritic, neuroprotective, and antiviral activity ( Zaragoza et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%